Analysis of volatile aroma constituents of wine produced from Indian mango (Mangifera indica L.) by GC-MS - Reddy, L. V. A. (Springer-Verlag, 2010)
Volatile aroma compounds are synthesized by wine yeast during wine fermentation. In this study the volatile aroma composition of two varieties of mango wine were determined to differentiate and characterize the wines. The wine was produced from the fruits of two varieties of mango cultivars namely Banginapalli and Alphonso. The volatile compounds formed in mango wine were analyzed by gas chromatography coupled with mass spectrometry (GC-MS). Thirty-two volatile compounds in wines were determined of which four were new and unidentified present in lower concentration. Apart from the ethanol (8.5 ± 0.28 and 7.2 ± 0.28% v/v), 1-propanol (54.11 ± 0.33 and 42.32 ± 0.57 mg/l), isobutyl alcohol (102 ± 1.57 and 115.14 ± 2.88 mg/l) and isoamyl alcohol (123 ± 2.88 and 108.40 ± 0.23 mg/1) were found to be the major flavouring higher alcohols in the mango wines produced from the fruits of Banginapalli and Alphonso respectively. Ethyl acetate (35 ± 0.57 and 30.42 ±1.15 mg/l) was the major ester component in both wines produced. Besides, other esters like ethyl octonoate, ethyl hexanoate and ethyl decanoate were also present in the wines. Cyclohexane methanol (1.45 ± 0.11 mg/l) was present only in wine made from Banginapalli and β-phenylethyl butanoate (0.62 ± 0.01 mg/1) was found only in Alphonso wine. The results demonstrate that the wine prepared from Banginapalli variety had better aroma composition and good taste than that from the Alphonso variety.